Development of Mobile Sales Force System for an Automotive Aftermarket Company - Michelle, Nastassja; Galinium, Maulahikmah; Eng, Kho I (Swiss German University, 2020)
The aftermarket automotive company has a set of documents that is called Customer Information Folder (CIF). The CIF is used by the salesmen to record every activity, observation and sales made with their customers. Currently, the CIF is a pile of papers, in which paper misplacement can occur and data can be mixed up, and salesmen must return to the office at the end of the day to write down what they have done. The objective of this research is to create a mobile sales force system with a web application back-end that can help the company handle customer data and the system can also assist in managing others such as sales, orders, stocks and commissions. Based on request from the company, an ERP system is planned to be developed, starting from customer data (CIF / SFA), orders, stocks and commissions, which are developed for this research. The result of this research shows that the new system can help provide and manage data relating to customers, orders, stocks and commissions. Secondly, the new system can reduce paper usage by half through the simulation. Thirdly, the new system can provide organized, accurate and trustworthy data. Fourthly, the new system can help the Sales Department and company owner in determining sales trends and buying trends. Lastly, the new system is shown to have fulfilled user expectation as there are positive gaps between expectation and perception.